Legislasi Agama Dan Potensi Ekonomi: Analisis Undang-Undang Nomor 41 Tahun 2004 Tentang Wakaf Di Indonesia - Ahmad Bisri Musthafa; fitri sariningsih (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2024)
Law Number 41 of 2004 concerning Waqf describes legislation rooted in religious principles. The consistency of this law with the principles of Scripture provides evidence of the government's seriousness in understanding the potential of waqf funds and the need for effective management. By regulating ontological, epistemological, and axiological aspects, this law is expected to improve economic welfare and strengthen the role of Muslims in the economic sphere. The importance of this law is undeniable, especially in providing legal certainty and the legal framework necessary for the management of waqf funds that have great potential, meeting the needs of the Wakif and the Nadzir.